(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents information on the food specialization of butterflies belonging to the Sphingidae family distributed in the conditions of South Fargo. According to the results of the research, 6 species of ghost butterflies have a polyphagous, 4 species have an oligophagous food spectrum. Ghost butterflies of the study area have trophic relationships with 44 species of plants belonging to 33 families. Including Agrius convolvuli 12 species belonging to 9 families, Smerinthus kindermannii 4 belonging to 1 family, Laothoe populi 10 belonging to 3 families, Macroglossum stellatarum 8 belonging to 6 families, Proserpinus proserpina 4 belonging to 3 families, Theretra Alecto 4 species belonging to 2 families, Hyles livornica 3 species belonging to 2 families, Hyles hippophaes 2 species belonging to 1 family, Hyles euphorbiae 4 species belonging to 3 families, Hylies zygophylli 3 species belonging to 2 families feed on plants.